National culture and sustainability disclosure practices: a literature review - Adedeji, Babatunji Samuel; Popoola, Oluwatoyin Muse Johnson; Tze, San Ong (OMJP Alpha Publishing, 2017)
The aim of this paper is to examine the extent to which national culture is an explanatory variable for firm’s disclosure choices for sustainable development in the advanced, emerging and developing nations of the world, especially that entities interact in globally knowledge-based economies. A review of theoretical and empirical studies carried out on some developed, emerging and developing nations was undertaken with particular reference to traits characterised in specific national cultural environments about their effects on sustainability disclosures. The reviews show that not much work had been done in this area of study, in particular concerning social and environmental disclosures. Furthermore, studies are in the developed nations as compared with the emerging and developing economies. The studies reviewed focused more on cross-national design with less attention on the longitudinal aspect. It was not possible to review papers that were not written in English language, just as it is also important to state that, not all published works were reviewed, especially with access denied to some online. There is a need for more empirical evidence to further justify the relevance of this study area for global sustainability disclosures and development. The review adds value with the recognition of the need to gear up researchers and policy making bodies to encourage advancement of studies on the intellectual capital concept and resource-based value theory to enhance sustainability development globally.